Diventare “mappe vive” - Glauco Barboglio (EtnoAntropologia)
This paper discusses the creation of a parish map in Casazza, Italy, that was started to revitalize the struggling Historical-Environmental Museum, spurring debate about local identity. The paper emphasizes the value of participatory approaches in shaping “shared heritage” as opposed to “institutional heritage”, advocating for the local Museum to adopt such approaches. Finally, it explores the role of anthropologists in local contexts, stressing the impact of anthropological methods in community engagement, especially where anthropology is not well known.